STRATEGI PENGOLAAN KELAS YANG EFEKTIF DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA DI MI MIFTAHUL FALAH RANDUSANGA KULON - Dwi Sulistiono; Taukhid Mubarok (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research aims to explain effective classroom teacher methods for improving students' disciplinary attitudes. In this research, a qualitative phenomenological approach was used; the subjects were a sixth grade teacher and several other teachers. Data was collected through interviews and observations. Then the data is analyzed by classifying, reducing, presenting and drawing conclusions. The research results show that teachers can improve students' disciplinary attitudes by optimizing classroom management, arranging seating well, playing voice intonation during learning, and ensuring that students arrive at class on time. Studies show that teachers' approaches to effective classroom management can improve students' disciplinary attitudes.